Embroidering Sustainability: A Review of Practices Aimed at Uplifting Chikankari Artisans in Lucknow, Uttar Pradesh (Journal of Advances and Scholarly Researches in Allied Education, 2025)
India is a major supplier of various handicrafts to the worldwide market. The Indian Chikankari business is highly esteemed in the worldwide handicraft market. This is an ancient culture and heritage of India that highlights many traditional arts from different parts of the country. Chikankari goods have a wide international market because of their growing potential. The Indian Chikankari industry is distinguished by its heavy dependence on manual labor and its decentralized structure, with production facilities situated in various rural and urban areas around the nation. The industry employs almost six million artisans, with a significant number being women and individuals from underprivileged groups. The Chikankari Sector exerts a significant and pivotal influence on the country's economy. The craft sector in rural and semi-urban regions provides employment to a substantial number of skilled workers and makes a considerable contribution to the country's foreign currency earnings, while also preserving its cultural heritage. Chikankari holds significant potential since it plays a vital role in sustaining the existing population of artisans across the whole country. Nevertheless, the substantial expansion of the Chikankari sector is accompanied by certain obstacles. The study highlighted the complexity and several obstacles associated with the Chikankari industry in India.